Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.5897/ajb11.025
|View full text |Cite
|
Sign up to set email alerts
|

Immunomodulatory effect of Rhaphidophora korthalsii on mice splenocyte, thymocyte and bone marrow cell proliferation and cytokine expression

Abstract: Rhaphidophora korthalsii methanol extract was previously found as a potential in vitro immunomodulating agent. In this study, the in vitro immunomodulatory activity of R. korthalsii methanol extract on mice splenocyte were quantified through evaluating T/NK cell population, cytokine expression (IL-2 and IFN-) and cytotoxicity against Yac-1 cell. In vitro MTT proliferation study showed that R. korthalsii methanol extract stimulate significant proliferation of splenocyte, thymocyte and bone marrow cell at 25 g/m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…Our finding is in line with the findings of Swee et al (2011) who reported that Rhaphidophora korthalsii methanol extract induced proliferation and activation of PBMCs, which in turn induce apoptosis of effector cancer cell (K562).…”
Section: Discussionsupporting
confidence: 93%
“…Our finding is in line with the findings of Swee et al (2011) who reported that Rhaphidophora korthalsii methanol extract induced proliferation and activation of PBMCs, which in turn induce apoptosis of effector cancer cell (K562).…”
Section: Discussionsupporting
confidence: 93%